2012
DOI: 10.1055/s-0032-1327241
|View full text |Cite
|
Sign up to set email alerts
|

Die Promotion in der Medizin ist besser als ihr Ruf

Abstract: More data from other medical faculties are needed to document the relevance of the medical dissertation to replace the emotional by a more rational debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…This gap suggests that a significant number of students do not feel that they gain sufficient scientific competencies during their doctorate. In contrast, other surveys conducted in Germany [26] have indicated that most students who have successfully submitted their thesis consider their work as beneficial and would recommend pursuing a doctorate to other students. Nevertheless, there are almost no published data on the fraction of students who have started but not completed their projects.…”
Section: Discussionmentioning
confidence: 85%
“…This gap suggests that a significant number of students do not feel that they gain sufficient scientific competencies during their doctorate. In contrast, other surveys conducted in Germany [26] have indicated that most students who have successfully submitted their thesis consider their work as beneficial and would recommend pursuing a doctorate to other students. Nevertheless, there are almost no published data on the fraction of students who have started but not completed their projects.…”
Section: Discussionmentioning
confidence: 85%
“…Taking this into consideration, it should not come as a surprise that percentages as high as 34% (Cohen et al [38]) and 31% (Dyrbye et al [29]) of voluntary medical student research were reported to result in first-authored Medline-indexed publications. Weihrauch et al and Pabst et al, on the other hand, reported favorable results in terms of the personal and professional value of the German dissertation requirement [124,125]. …”
Section: Resultsmentioning
confidence: 99%
“…The present questionnaire does not specifically ask for the PubMed-listing which could be a reason for the discrepant results. Beyond that Pabst et al recently showed that self-reported publications yield better results than an internet based survey [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, every doctor needs to learn how new findings are gained, which methods are used and how the quality of scientific publications can be assessed [8]. In addition, two recent publications show that the German medical dissertation is better than its reputation [9], [10]. Depending on whether the data were collected via online survey or voluntary disclosure, 52% and 62% respectively of the doctoral candidates publish their results in scientific journals and 25% even publish as first author.…”
Section: Introductionmentioning
confidence: 99%